Struktur Komunitas Dermaptera Predator Pada Tanaman Kelapa Sawit - Efendi, Siska; Setiawati, Rahmi; Suhendra, Dede; Awaluddin, Awaluddin (JURNAL AGROPLASMA, 2023)
This research observed about the structure of Dermaptera insects community on oil palm trees. This research is aimed to study about the structure of the community and the abundance of each species of Dermaptera on oil palm trees. The research is conducted in three places, they are Nagari Gunung Selasih, Sungai Dareh and IV Koto. The research is conducted using hand collecting method once a month. It is operated two times in October and November 2017. Result shows that there are four species of Dermaptera found in the three places, they are Chelisoches morio, Doru aculeatum, Euborellia arcanum and Vostox apicedentatus. The most common species found is C. morio. It is also found that the structure of Dermaptera is not complex because itâ€™s unevenness and has a low biodiversity value.Â